School Social Worker Views on the Current State of Safety in U.S. Schools: A Qualitative Study. Issue 1 (22nd November 2018) - Cuellar, Matthew J; Mason, Susan E
Abstract: The purpose of this study was to examine the shared concerns and remedies school social workers have about safety in their schools. A sample of school social work practitioners across the United States ( N = 260) provided a response to the qualitative prompt: "In general, how do you think school safety in the United States can be improved?" An inductive, thematic study of pre-existing data was conducted to determine the aspects of school safety most concerning to participants. Through open, axial, and selective coding, three salient themes for increasing school safety emerged: (1) increase training and services, (2) focus on school–community partnerships, and (3) advocate for policy and school structural changes that affect school safety. Findings from this study indicate social workers' concern for school safety and their willingness to assist with needed improvements. The article concludes with a discussion of implications for practice and recommendations for future research.